Inactivation of severe acute respiratory syndrome coronavirus 2 in plasma and platelet products using a riboflavin and ultraviolet light‐based photochemical treatment - Keil, Shawn D.; Ragan, Izabela; Yonemura, Susan; Hartson, Lindsay; Dart, Nicole K.; Bowen, Richard (Vox sanguinis, 2020)
Background and Objective Severe acute respiratory distress syndrome coronavirus‐2 (SARS‐CoV‐2), the causative agent of coronavirus disease 2019 (COVID‐19), is a member of the coronavirus family. Coronavirus infections in humans are typically associated with respiratory illnesses; however, viral RNA has been isolated in serum from infected patients. Coronaviruses have been identified as a potential low‐risk threat to blood safety. The Mirasol Pathogen Reduction Technology (PRT) System utilizes riboflavin and ultraviolet (UV) light to render blood‐borne pathogens noninfectious, while maintaining blood product quality. Here, we report on the efficacy of riboflavin and UV light against the pandemic virus SARS‐CoV‐2 when tested in both plasma and platelets units. Materials and Methods Stock SARS‐CoV‐2 was grown in Vero cells and inoculated into either plasma or platelet units. Those units were then treated with riboflavin and UV light. The infectious titres of SARS‐CoV‐2 were determined by plaque assay using Vero cells. A total of five (n = 5) plasma and three (n = 3) platelet products were evaluated in this study. Results In both experiments, the measured titre of SARS‐CoV‐2 was below the limit of detection following treatment with riboflavin and UV light. The mean log reductions in the viral titres were ≥3·40 and ≥4·53 for the plasma units and platelet units, respectively. Conclusion Riboflavin and UV light effectively reduced the titre of SARS‐CoV‐2 in both plasma and platelet products to below the limit of detection in tissue culture. The data suggest that the process would be effective in reducing the theoretical risk of transfusion transmitted SARS‐CoV‐2.